Primary moult of continental Black-tailed Godwits Limosa limosa limosa in the Doñana wetlands, Spain. Issue 1 (2nd January 2018) - Márquez-Ferrando, Rocío; Remisiewicz, Magdalena; Masero, Jose A.; Kentie, Rosemarie; Senner, Nathan; Verhoeven, Mo A.; Hooijmeijer, Jos C.E.W.; Pardal, Sara; Sarasa, Mathieu; Piersma, Theunis; Figuerola, Jordi
ABSTRACT: Capsule: Most Continental Black-tailed Godwits Limosa limosa limosa using the Doñana wetlands during post-breeding migration appear to begin moult before they arrive and suspend moult before they migrate onwards to West Africa. Aims: We aim to describe the primary moult strategies and patterns in the Continental Black-tailed Godwits using the Doñana wetlands, a major passage and wintering area for waterbirds in southern Spain. Methods: Individual godwits were captured, marked and their primary moult was scored in Doñana during the non-breeding season (June–March) in 2011 and 2012. Data from resightings of colour-marked godwits and birds equipped with satellite transmitters were used to estimate stopover duration during post-breeding migration (June–September) to determine if godwits move to West Africa before completing their primary moult. Results: Average primary moult duration was estimated to be 84 days ± 9 se, during 29 June–21 September and did not differ between sexes. Only 2% of individuals were observed with suspended moult. We estimated stopover duration in Doñana to be 13 days ± 2 se before migrating to West Africa. Conclusions: Most godwits stage for about two weeks in the Doñana wetlands during southward migration, moult their primaries and appear to suspend moult before crossing the Sahara. Others may complete their primary moult in Doñana, or elsewhere in Europe and overwinter in Doñana where increasing numbers of godwits have been detected in recent years. A few individuals may finish the moult in Doñana and migrate to West Africa late in the post-breeding season.